(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Inventory control is one of the most important tasks for industrial companies. Inventory control systems play an important role in inventory monitoring. Wireless Sensor Networks (WSNs) technology has been taken into great attention in the field of inventory control because it is considered as an efficient, low-cost technology to control inventories. This paper proposes an intelligent inventory control system depending on WSNs and fuzzy logic to control the dependent demand items effectively under MRP system and L4L lot sizing rule. to be used to solve the industrial problems. A numerical example of a 5 drawers - chest of drawers product has been experimented. The advantage of the proposed WSN-FL4L system could be represented in its ability to make decisions in different inventory states. Different cases of replenishment were investigated depending on the (IF-THEN rules) statement of fuzzy logic. Ultrasonic - distance sensor has been programmed to compute the number of items’ pieces, depending on the thickness of each piece. ASP.net web application and C# programming language based on SQL database server are applied.